Capricornio y el natalicio de Augusto - Alberto González García (Revista Numismática Hécate, 2014)
This paper aims to demonstrate that Augustus was born in astronomical December, under the sign of Capricorn, in a date that was equivalent to calendarical September because of the traditional inaccuracies of the Roman calendar with respect to astronomical reality, as well as remark the weakness of all the other theories proposed on this question.